Vocabulary Teaching Strategies Used by Teachers at SMPN 264 Jakarta - Miranda, Khoerunnissa; Arianti, Theresia (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This research is a study to describe the strategies used by teachers in teaching vocabulary. This study is important to be conducted because learning vocabulary is basic to raw building blocks that students can use to express their thoughts, and ideas and share information in both oral and written form. Previous studies on this topic have been conducted but none has been conducted at SMPN 264. This is the gap that is fulfilled by the current study. The current study was conducted at SMPN 264 Jakarta Barat. The aim of the study is to find out the strategies used by teachers in teaching vocabulary. This study used a case study on vocabulary teaching strategies as the methodology. The finding shows that the most frequently used strategy by teachers at SMPN 264 Jakarta is translating, while memorization is the least used strategy.